Pengaruh Literasi Keuangan, Sikap Keuangan dan Pengetahuan Keuangan Terhadap Perilaku Manajemen Keuangan Mahasiswa Jurusan Akuntansi Universitas Islam Malang Angkatan Tahun 2019 - Muhammad Syahrevi Alfitra; Arista Fauzi Kartika Sari; Hariri Hariri (Universitas Islam Malang, 2023)
In this world money is always related to humans in everyday life to meet their needs. In the use of money, there are differences between one and the other so that some are wise to use money properly and some are not. To avoid bad financial control, one must manage finances well. The purpose of this study was to determine the effect of financial literacy, financial attitudes and financial knowledge on financial management behavior of students majoring in accounting at the Islamic University of Malang. Sampling obtained 80 respondents based on the criteria applied. This study uses a multiple linear regression model. The results of this study indicate that Financial Literacy, Financial Attitudes and Financial Knowledge have a significant positive effect on Financial Management Behavior. Financial Literacy has a significant positive effect on Financial Management Behavior. Financial Attitude has no significant effect on Financial Management Behavior. Financial Knowledge has a significant positive effect on Financial Management Behavior.Keywords: Financial Literacy, Financial Attitude, Financial Knowledge, Financial Management Behavior.